Housing and Cooling Strategies to Mitigate Heat Stress and Enhance Broiler Performance in Humid Tropical Climates: A Systematic Review - Akhmat Rizkuna; Dani Nur Arifin; Amani Aldiyanti (CV. Komunitas Dunia Peternakan, 2026)
Heat stress is a major constraint in broiler production systems located in humid tropical climates, where high ambient temperature and relative humidity impair growth performance, feed efficiency, and animal welfare. This systematic review synthesizes peer-reviewed studies published between January 2015 and December 2025 evaluating environmental housing designs and cooling strategies for mitigating heat stress in broiler chickens. This systematic review followed the PRISMA 2020 guidelines and synthesized peer-reviewed studies retrieved from Scopus, Web of Science, and ScienceDirect, published between January 2015 and December 2025. From 500 records initially identified, 26 studies fulfilled the predefined eligibility criteria and were included in the qualitative synthesis. The findings demonstrate that evaporative cooling systems, tunnel ventilation, and automated climate control technologies consistently reduced indoor temperature (2–6°C) and improved body weight gain, feed conversion ratio (FCR), and mortality rates under hot-humid conditions. However, cooling efficiency was strongly influenced by ambient humidity, necessitating integrated and adaptive environmental control approaches. Smart sensor-based systems further enhanced microclimate stability and thermal uniformity within broiler houses. Beyond performance improvements, optimized environmental management reduced physiological stress indicators, including heterophil-to-lymphocyte ratios and corticosterone levels. Overall, integrated, humidity-adaptive, and energy-efficient cooling strategies are essential to sustain productivity, welfare, and climate resilience in tropical broiler production systems.